Mapping the Sufi Ethics of the Self: A Study of Seven Virtues and Vices in Serat Nitiprana within Javanese Islam - Bistara, Raha; Jali, Hasan bin (Tashwirul Afkar, 2024)
This study aims to analyze the Sufi ethical system in Serat Nitiprana by Kiai Yasadipura I by examining the construction of seven virtues and seven vices as a framework of ethical selfhood within the Javanese-Islamic cultural context. The research responds to the growing moral disorientation and spiritual crisis among contemporary Javanese Muslims by revisiting a classical spiritual text that integrates Sufi teachings with local pedagogical strategies. Using a qualitative textual analysis approach, this study examines the macapat poetic structure of the manuscript to identify patterns of moral symbolism and spiritual instruction. The findings reveal that Serat Nitiprana systematically constructs a dualistic moral framework: virtues such as patience, humility, and self-awareness serve as progressive maqāmāt (spiritual stations), while the vices, framed as nafs impulses and satanic temptations, represent barriers in the sulūk (spiritual journey). Furthermore, the text outlines a vision of insān kāmil (the perfect self) through symbolic idioms like sangkan paraning dumadi and sedulur papat lima pancer, articulating a deeply localized Sufi cosmology. These results imply that classical Javanese Sufi literature can serve as a contextual tool for moral and spiritual education amid the erosion of traditional values. The originality of this study lies in its systematic mapping of oppositional moral elements in Serat Nitiprana, which, unlike previous historical or philological studies, interprets the text as a comprehensive and localized Sufi ethical system that remains relevant for contemporary pedagogical and spiritual discourse.